Light-curing Time and Aging Effects on the Nanomechanical Properties of Methacrylate- and Silorane-based Restorations - Catelan, A.; Pollard, T.; Bedran-Russo, A. K.; Santos, Paulo Henrique dos [UNESP]; Ambrosano, G. M. B.; Aguiar, F. H. B. (Operative Dentistry Inc, 2014)
The aim of this study was to assess the influence of light-curing time on the nanohardness (H) and reduced elastic modulus (E-r) of components (underlying dentin, hybrid layer, adhesive, and composite) of methacrylate- and silorane-based restorations after 24 hours and six months of storage. Class II slot preparations were carried out in human molars (n=3) and restored with methacrylate (Clearfil SE Bond [Kuraray] + Filtek Z250 [3M ESPE]) or silorane (LS restorative system [3M ESPE]) restorative systems and light-cured using light-emitting diode at 1390 mW/cm(2) for the recommended manufacturers' time or double time. Restorations were sectioned, and bonded dentin-resin interfaces were embedded in epoxy resin and polished for evaluation with a Berkovich fluid cell tip (TI 700 Ubi-1 nano-indenter, Hysitron). Data were statistically analyzed by analysis of variance and Tukey's test (alpha=0.05). Overall, the H and E-r values were higher for methacrylate-based restorations than for silorane materials (p <= 0.05), an increase in curing time did not improve the H and E-r of the bonded interface components of either material (p>0.05), and aging significantly decreased the mechanical properties of interface components of both resin-based restorative systems (p <= 0.05). In general, nanomechanical properties decreased after six months of storage, the methacrylate restorative system exhibited higher H and E-r than silorane, and light-curing time did not influence the properties tested.